Klotildaren miraria "Klobis" pastoralean - Loidi Garitano, Ane (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
In this work, we present a small sample of the Soule Pastoral. We give two texts that narrate the same fragment of the work Klobis, taken from the XVIIIh and the XIXth century manuscripts. The strophes we have chosen decribe the miracle carried out by Klotilda, King Clovis' wife. Our objective is to compare both parts. On the other hand, this work is an attempt to provide a solution to the problems that appear when transcribing this type of text into current orthography.